2016
DOI: 10.1016/j.seizure.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

CBD-enriched medical cannabis for intractable pediatric epilepsy

Abstract: The results of this multicenter study on CBD treatment for intractable epilepsy in a population of children and adolescents are highly promising. Further prospective, well-designed clinical trials using enriched CBD medical cannabis are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
167
0
15

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(187 citation statements)
references
References 21 publications
5
167
0
15
Order By: Relevance
“…Participants were given a standardized breakfast, and 15 minutes later, they were given either oral CBD (600 mg) or placebo in a double-blind fashion. This is a dose known to cause anxiolytic effects in humans and is comparable with what is used clinically (19,(37)(38)(39). Study medication consisted of capsules containing either 100 mg of CBD or excipients, which were a gift from GW Pharmaceuticals.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were given a standardized breakfast, and 15 minutes later, they were given either oral CBD (600 mg) or placebo in a double-blind fashion. This is a dose known to cause anxiolytic effects in humans and is comparable with what is used clinically (19,(37)(38)(39). Study medication consisted of capsules containing either 100 mg of CBD or excipients, which were a gift from GW Pharmaceuticals.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have administered oral doses (≤600 mg) of CBD to healthy participants with little to no marijuana use histories and have reported minimal side effects (Bergamaschi et al, 2011; Bhattacharyya et al, 2010; Cunha et al, 1980; Hollister, 1973; Karniol et al, 1974; Zuardi et al, 1993). Oral CBD has been tested in clinical populations (Huntington's disease, epilepsy patients) at much higher cumulative doses (e.g., 1280 mg/day; 50 mg/kg/day) with reports of somnolence, decreased appetite/weight loss, diarrhea and increased seizure in a small subset of epilepsy patients (Consroe et al, 1991; Devinsky et al, 2016; Tzadok et al, 2016). Despite the frequent statements in the media and the scientific literature that CBD is void of psychoactive effects, this has never been formally assessed – no studies have completed an abuse liability assessment, enrolled the population of interest (marijuana users) or compared CBD effects to a cannabinoid agent with known abuse liability, such as smoked marijuana, as a positive control.…”
Section: Introductionmentioning
confidence: 99%
“…It has low affinity to the CB1 (neuronal) and CB2 (found mainly in the body's immune system) receptors. [7][8][9][10] In fact, the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) have granted CBD preparations the "orphan drug" designation for use in the treatment of epilepsy in children (Dravet and Lennox-Gastaut syndromes) and neonatal asphyxia. 4 In vitro and in vivo preclinical research has shown that CBD has several potential effects on therapeutic applications: it possesses antiseizure, antioxidant, neuroprotective, anti-inflammatory, analgesic, antitumor, antiemetic, antipsychotic, and antianxiety activities.…”
mentioning
confidence: 99%